UPAYA INDONESIAN DIASPORA NETWORK (IDN) DALAM DIPLOMASI PUBLIK INDONESIA TERHADAP BELANDA DI BIDANG SOSIAL BUDAYA TAHUN 2013-2016 - Ayu Angelina Aritonang; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This thesis is an international relations research in diplomacy studies which describes about the efforts of Indonesian diaspora network Netherland (IDN-NL) in Indonesian’s public diplomacy toward Netherland in social culture aspect n 2013-2016. Indonesia and Netherland have long history, from conflict till cooperation. To maintain this good term relations, Indonesia conduct public diplomacy. The successes of Indonesia’s public diplomacy can be affected by the interaction of Indonesian public with Netherland public. IDN-NL as an Indonesia’s interactions tool is expected give some positive impacts.This is qualitative research which used descriptive methods, and collecting data from books, journals, official publications and relevant websites. This paper used the neo-realist perspective and multi-track diplomacy theory proposed by John Mc. Donald and Louise Diamond. The object of this research is Indonesian diaspora network Netherland.The result of this research shows that IDN-NL creates some programs and activities that involve Indonesian and Netherland in social culture aspect. The programs and activities held by the task forces and give some positives impacts to Indonesian diplomacy toward Netherland.Key Words: IDN, IDN-NL, Public Diplomacy, Neo-Realist.